IMPORTANCE OF THE PROFESSIONAL OF PHYSICAL EDUCATION IN THE RECOVERY AFTER TREATMENT OF THE LESSON OF THE PREVIOUS CROSS LINK (LCA) (Fiep Bulletin - online, 2018)
In the last decades several studies have been focused on the early diagnosis of the ACL lesion and indication of themost appropriate treatment. The knee is formed by the femur, tibia and patella that constitute a complex joint constantly subject tothe action of the corporal weight whose stability depends on the relation between the bony anatomy, the muscular activity andligamentar. The bones are connected by ligaments, four of which are the main function of which is to keep the bones together andthe knee stable. The lesion of the anterior cruciate ligament is very serious because the ligament has the function of keeping thetibia back in relation to the femur and, when it breaks, it moves forward. The objective of this research was the anterior cruciateligament injury, its forms of occurrence, treatments and, the importance of the physical trainer's participation in the rehabilitationprocess of this patient. The theoretical basis was elaborated using articles, periodicals, complete texts, dissertations and thesessearched in the Scientific Electronic Library Online (Scielo), Lilacse Google Scholar and CESUFOZ library platforms. Thekeywords or descriptors were: Anterior cruciate ligament injury (ACL), prevention, proprioceptive exercises, treatment,rehabilitation, physical trainer. The results showed that the most used treatments were conservative with strengthening of thequadriceps and posterior of the thigh, with the aid of bracing, proprioception works and hydrotherapy. It was concluded that thephysical trainer should act in a preventive way and in the process of rehabilitation of the lesions of the anterior cruciate ligament ofthe knee, being the work of strengthening, proprioception and hydrotherapy with emphasis on the lower limbs the most used.
Keywords: Anatomy; knee; lesion